Social Media Influencer: The Influence of Followers’ Purchase Intention through Online Engagement and Attitude - Giovanni Imanuel Dauhan; Edwin Langi (Binus Business Review, 2024)
Marketing collaboration with social media influencers is rapidly developing into a promotional strategy. It is considered the most effective for marketers worldwide, including in Indonesia. Although effective, marketers face challenges in selecting the right Social Media Influencer (SMI) according to the company’s brand due to the high growth in the number of SMIs. The research aimed to examine the relationship between the influence of SMI credibility based on the source credibility model and the advertising value of SMI content on attitude toward SMI and online engagement. Then, it led to purchase intention as a determinant of the success of product/brand promotion activities. The research used the Stimulus-Organism-Responses (SOR) framework. The number of samples used was 261 social media users who followed at least one SMI and were domiciled in several regions of Indonesia. Partial Least Square Structural Equation Model (PLS-SEM) was used as a data analysis method, with software analysis tools of Smart PLS Ver.3.2. The results show that SMI’s credibility based on the source credibility model and content value based on advertising value act as a stimulus. They have a significant and positive effect on followers’ attitude and online engagement. They also subsequently influence purchase intention. Both attitude toward SMI and online engagement mediates the relationship between source credibility and the advertising value of content on purchase intention. These findings can help marketers’ strategies in determining the right SMI to use.